2016
DOI: 10.4269/ajtmh.15-0703
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Helminth Infections, Plasmodium falciparum Parasite Carriage and Antibody Responses to Sexual and Asexual Stage Malarial Antigens

Abstract: Abstract. Infections with helminths and Plasmodium spp. overlap in their geographical distribution. It has been postulated that helminth infections may influence malarial transmission by altering Plasmodium falciparum gametocytogenesis. This cross-sectional study assessed the effect of helminth infections on P. falciparum gametocyte carriage and on humoral immune responses to sexual stage antigens in Gabon. Schistosoma haematobium and filarial infections as well as P. falciparum asexual forms and gametocyte ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…38 We found that children infected 20 However, two other studies found discordant results. 18,19 In a Senegalese cohort, Courtin and coll. found that levels of IgG directed to GLURP and MSP-1 were lower in Sh-infected children than in those uninfected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 We found that children infected 20 However, two other studies found discordant results. 18,19 In a Senegalese cohort, Courtin and coll. found that levels of IgG directed to GLURP and MSP-1 were lower in Sh-infected children than in those uninfected.…”
Section: Discussionmentioning
confidence: 99%
“…Studies concerning the impact of schistosomiasis on anti‐ Pf antibody (Ab) responses are limited. Five studies have analysed anti‐ Pf Ab responses during schistosome infection . Three of them documented lower levels of IgG with specificity for Pf candidate vaccine antigens or crude schizont extracts in Sh ‐infected individuals .…”
Section: Introductionmentioning
confidence: 99%
“…Recent published data demonstrate that the prevalence in the area for S . haematobium range from 15% to 75% [ 9 , 13 , 14 ]. Water supply, fishing, household work, fetching water and playing are some activities which expose the local population to schistosomiasis.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study conducted in the vicinities of Lambaréné reported a 42% prevalence for plasmodium infection among school age children [ 9 ]. To be able to detect a minimum of 12.5% prevalence difference of plasmodium infection between children with schistosomiasis and those without, with a minimum of 80% power, we needed to include in the study at baseline at least 249 children for each study group, giving a total of 498 volunteers school age children.…”
Section: Methodsmentioning
confidence: 99%
“…In Gabon, malaria and intestinal parasite infections (IPIs) as well as lariasis are frequently diagnosed in the population, with the prevalence varying from 1% to 75% [1,2]. This geographical co-distribution can lead to polyparasitism with possible interactions between parasite species.…”
Section: Introductionmentioning
confidence: 99%